Maintaining the Quality of Kacang Buck Semen in Chilled Storage with the Addition of Green Tea Extract in Extender - Susilowati, S.; Mustofa, I.; Wurlina, W.; Hernawati, T.; Oktanella, Y. (Tropical Animal Science Journal, 2021)
Kacang goats can be bred through artificial insemination techniques using liquid semen from a superior buck. The study was aimed to determine the quality of Kacang buck semen in chilled storage when green tea extract (GTE) was added to the semen extender. Specifically, 12 ejaculates from three Kacang bucks were diluted in skim milk–egg yolk extender containing 0 mg, 0.05, 0.10, and 0.15 mg of GTE/100 mL. The extended semen was stored at 5°C, and its quality was evaluated daily for 5 d. Comparatively, semen with 0.10 mg of GTE/100 mL had the best quality (p